AN ANALYSIS ON COHESION IN EDGAR ALLAN POEâS SHORT STORY âTHE FALL OF THE HOUSE OF USHERâ - Sari, Yulvi Triana (Jurnal Bahasa Lingua Scientia, 2016)
The devices function as a way of getting text âhang togetherâ as a whole as well as indicators of text unity. The organization of those devices are categorized as cohesion which is also considered as one of the elements helps the readers to be able to perceive and interpret language well especially in written form. The present study aims to identify the types of cohesion found and the most frequently used in Edgar Allan Poeâs short story which occur within sentences, between sentences and between paragraphs. The fndings reveal that the types of cohesion found are grammatical cohesion which comprises reference, ellipsis, substitution and conjunction, the most frequently used is reference between sentences. Meanwhile, on the lexical cohesion which cover reiteration and collocation, it is found that the most widely found is reiteration namely synonymy between paragraphs.